Effect of mixed spices on hyperglycemia & lipid profile in case controlled Type 2 Diabetes Mellitus (T2DM): a preliminary report - Mahmood, Tahir; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani; Azam, Siti Amirah; Shamsudin, Nural Aimi (Global Science and Technology Forum (GSTF), 2014)
Despite a considerable progress in the treatment of Type 2 Diabetes Mellitus (T2DM), it remains a major medical challenge in the 21st century, threatening the health and economy of all nations particularly the developing countries. Spices which are added to the preparation of diets for taste and aroma have been shown to be effective in the control of hyperglycemia both in animals and human studies. In this study, 20 patients were recruited from the Medical Out-patient Department of Hospital Tengku Ampuan Afzan Kuantan, Malaysia. The study protocol was approved by the International Islamic Medical University Malaysia Research Ethical Committee and the Clinical Research Committee (CRC) Ministry of Health Malaysia. 10 patients were provided with the Placebo and another 10 patients were served with 4 g of mixed spices daily for 30 days. Blood samples were collected before and at the end of the feeding period and analyzed for the parameters namely Fasting Blood Sugar (FBS), post-prandial blood sugar (2HPP), Glycosylated Haemoglobin (HbA1c) and Lipid Profile. The collected data was analyzed using SPSS Statistical Software version 12. All the patients tolerated mixed spices very well and showed an improvement in their general well being. The blood results showed a significant improvement in FBS and total cholesterol (p<0.05). This preliminary clinical trial shows that the formulated spices have positive effect in T2DM patients. - See more at: http://dl4.globalstf.org/?wpsc-product=effect-of-mixed-spices-on-hyperglycemia-lipid-profile-in-case-controlled-type-2-diabetes-mellitus-t2dm-a-preliminary-report#sthash.nbWHH4MH.dpuf